TYPE 1 DIABETES AND ANXIETY IN PEDIATRICS: AN INTEGRATIVE REVIEW - Machado de Oliveira, Keuliane (2023)
To identify studies in the literature that discuss the association between diabetes mellitus and anxiety in children and adolescents. This is an integrative review constructed by crossing the following Health Science Descriptors (DeCS/MeSH): "Diabetes Mellitus type 1"; "Anxiety"; "Adolescent"; "Child" and their English counterparts "Type 1 Diabetes Mellitus", "Anxiety", "Children", and "Adolescent". The terms were linked using the boolean indicators "and" or "e". Manuscripts published between 2019 and 2023 in Portuguese and English languages were considered. Twelve studies were included, which demonstrate the emotional distress experienced by children, adolescents, and their parents/caregivers in response to the demands imposed by type 1 diabetes mellitus. The review has shown that anxiety is present in both children/adolescents with type 1 diabetes and their parents, highlighting the importance of emotional support to cope with the demands imposed by this chronic condition.